Decoupled linkage between soil carbon and nitrogen mineralization among soil depths in a subtropical mixed forest. (June 2017) - Tian, Qiuxiang; Wang, Xinggang; Wang, Dongya; Wang, Min; Liao, Chang; Yang, Xiaolu; Liu, Feng
Abstract: Deep soil stores a large amount of organic carbon (C) and nitrogen (N). However, little is known regarding the interactions between soil C and net N mineralization in deep soil, which complicates the prediction of ecosystem C and N dynamics. In this study, a 150-day laboratory soil incubation experiment was performed under 20 °C and 25 °C to investigate the influence of soil depth and warming on C and net N mineralization and their relationship. Soils were collected from a Hapludalfs profile in a subtropical forest with three depth intervals: 0–10 (topsoil), 10–30 (midsoil), and 30–60 cm (subsoil). Soil microbial community-level physiological profiling (CLPP) was conducted to investigate the role of the microbial community in C and N mineralization. The results demonstrated that both C and net N mineralization rates in subsoil were significantly lower than in topsoil. Compared to topsoil, subsoil had lower temperature sensitivity of C mineralization and relatively higher temperature sensitivity of net N mineralization. Cumulative soil C and net N mineralized were positively correlated in topsoil with the mineralized N per mineralized C showed as 0.19 and 0.31 at 20 °C and 25 °C, respectively. However, there was no significant correlation between cumulative soil C and net N mineralized in subsoil due to the low amount of net N mineralization. The lack of labile C source and degradable organic N were believed to limit the net N mineralization in subsoil. The microbial community in topsoil used relatively more easily decomposable carbohydrates and carboxylic acids, which favored C mineralization. In contrast, the microbial community in subsoil had relatively high utilization of amino acids (N-containing substrates), which indicated there was N limitation. This distinguished substrate utilization patterns of microbial communities could explain the observed C and N mineralization rates among the soil depths, and suggests that the microbial community played an important role in soil C and N mineralization. The decoupled relationships between soil C and net N mineralization in deep soil and their differentiated responses to warmer temperatures among soil depths indicated that deep soil should be considered separately from topsoil for ecosystem C and N cycling, especially for ecosystem C dynamic models. Highlights: Both C and net N mineralization were significantly lower in subsoil than in topsoil. Soil C and net N mineralization were positively correlated in topsoil, but not in subsoil. The lack of labile C and degradable organic N limited net N mineralization in subsoil. The quality and quantity of soil C and N sources regulate soil microbial community.